Web-Based appointment system using short message service technology: Usability aspect - Abd Wahab, Mohd Helmy; Ooi, Lee Lee; Abdul Mutalib, Ariffin; Hassan, Norlida; Mohd Sidek, Roslina; Mohamad Mohsin, Mohamad Farhan (2010)
This paper presents an ongoing research that helps students and lecturers to be always aware of the appointment no matter where they are.It contributes to the teaching and learning process, in which communication is made easy using short messaging system (SMS) technology.It starts with examples of previous success stories of the implementation of SMS in many areas.The objectives of the paper are to discuss about the hardware and software requirement, and integrate them to be measured in terms functional. The research method is outlined next, and some discussions on current outcome of the research are addressed.The research is planned to be continued with full implementation of the proposed system that is called Student Appointment System using SMS technology.